A Modulated Complex Lapped Transform and its Application to Audio Processing - Malvar, Henrique S. (Institute of Electrical and Electronics Engineers, Inc., 1999)
This paper introduces a new structure for a modulated complex lapped transform (MCLT), which is a complex extension of the modulated lapped transform (MLT). The MCLT is a particular kind of a 2x oversampled generalized DFT filter bank, whose real part corresponds to the MLT. That property can be used for efficient implementation of joint echo cancellation, noise reduction, and coding, for example. Fast algorithms for the MCLT are presented, as well as examples that show the good performance of the MCLT in noise reduction and echo cancellation.